2019
DOI: 10.5152/tud.2019.19038
|View full text |Cite
|
Sign up to set email alerts
|

Can magnitip double-J stent serve as a substitute for a standard double-J stent?

Abstract: printing of pelvic fracture urethral injuries-fusion of technology and urethroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…This allowed the magnet to move and turn around more easily, thus facilitating contact with the urethral retrieval catheter's magnet, regardless of the position of the distal J. As a result of this improvement, the authors reported a stent removal success rate of 97% (9) , consistent with the latest studies available in the literature (10)(11)(12) .…”
Section: Discussionsupporting
confidence: 75%
“…This allowed the magnet to move and turn around more easily, thus facilitating contact with the urethral retrieval catheter's magnet, regardless of the position of the distal J. As a result of this improvement, the authors reported a stent removal success rate of 97% (9) , consistent with the latest studies available in the literature (10)(11)(12) .…”
Section: Discussionsupporting
confidence: 75%
“…[4–6,8,13,14] Two studies found that postoperative morbidity related to MEDJUS use was significant. [7,8] However, two other studies reported that postoperative morbidity was not statistically significant. [4,5]…”
Section: Resultsmentioning
confidence: 99%
“…Traditional double-J ureteral stents are commonly used to maintain ureteral patency; however, they have been associated with a multitude of complications during the stent indwelling period and subsequent removal. [7,14]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations